A Simple and Rapid Synthesis of Spherical Silver Phosphate (Ag3PO4) and Its Antimicrobial Activity in Plant Tissue Culture - Laohavisuti, Nongnuch; Boonchom, Banjong; Rungrojchaipon, Pesak; Boonmee, Wimonmat; Seesanong, Somkiat; Punthipayanon, Sirichet (My University, 2025)
A simple and rapid precipitation process was successfully employed to prepare silver phosphate (SP, Ag3PO4). Two different phosphate sources: diammonium hydrogen phosphate ((NH4)2HPO4) and dipotassium hydrogen phosphate (K2HPO4) were applied separately as the precursor, obtaining ((NH4)2HPO4)− and K2HPO4− derived SP powders, named SP-A or SP-P, respectively. Fourier transform infrared (FTIR) spectra pointed out the vibrational characteristics of P–O and O–P–O interactions, confirming the presence of the PO43– functional group for SP. X-ray diffraction (XRD) patterns revealed that the SP crystallized in a cubic crystal structure. Whereas the field emission scanning electron microscope (FESEM) exposed spherical SP particles. The potentially antibacterial activity of SP-A and SP-P against bacterial Bacillus stratosphericus, yeast Meyerozyma guilliermondii, and fungal Phanerodontia chrysosporium was subsequently investigated. All studied microorganisms were recovered and isolated from the aquatic plant during the tissue culture process. The preliminary result of the antimicrobial test revealed that SP-A has higher antimicrobial activity than SP-P. The superior antimicrobial efficiency of SP-A compared to SP-P may be attributed to its purity and crystallite size, which provide a higher surface area and more active sites. In addition, the presence of potassium-related impurities in SP-P could have negatively affected its antimicrobial performance. These findings suggest that SP holds potential as an antimicrobial agent for maintaining sterility in tissue cultures, particularly in aquatic plant systems. The growth of both B. stratosphericus and M. guilliermondii was suppressed effectively at 30 ppm SP-A, whereas 10 ppm of SP-A can suppress P. chrysosporium development. This present work also highlights the potential of SP at very low concentrations (10–30 ppm) for utilization as an effective antimicrobial agent in tissue culture, compared to a commercial antimicrobial agent, viz., acetic acid, at the same concentration.
Keywords: antibacterial activity; microorganism; silver phosphate; tissue culture